IMPROVING READING COMPREHENSION ACHIEVEMENT BY USING PROJECT-BASED LEARNING (PBL) STRATEGY - Mayang Jingga; Umar Abdullah; Husnaini (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
Reading is a fundamental skill that enhances comprehension, critical thinking, and effective communication. However, many tenth-grade students at senior high schools in Palembang struggle with reading comprehension, which negatively impacts their academic performance. Addressing these challenges is essential to improving literacy and cognitive skills. To bridge this gap, the researcher conducted a quasi-experimental investigation into the effectiveness of Project-Based Learning (PBL) using storyboard media to enhance reading instruction. The study aimed to determine whether PBL with storyboards led to a significant difference in reading comprehension compared to traditional methods and whether students showed measurable improvement after the intervention. A pretest and post-test non-equivalent groups design was employed, involving 64 students from two different classes. Data were collected through pretests and post-tests and analyzed using independent sample t-tests and paired sample t-tests in SPSS 26. The results provided compelling evidence of the intervention’s effectiveness. The independent sample t-test yielded a highly significant p-value of 0.000 and a t-value of 4.855, confirming a substantial difference between the experimental and control groups. Additionally, the paired sample t-test revealed a p-value of 0.000 and a t-value of 22.272, demonstrating a significant improvement in students’ reading comprehension after the intervention. These findings highlight the potential of PBL with storyboard media as an effective instructional approach to enhance students’ reading comprehension